Macrogenetics Approach Reveals Spatial Trends and Drivers of Mitochondrial Genetic Diversity at Different Biological Organization Levels in Tropical Western Atlantic Decapods - Pedro A. Peres; Fernando L. Mantelatto (Ecology and Evolution)
ABSTRACT Recent studies explored whether the latitudinal diversity gradient extends to a latitudinal genetic diversity gradient. There is a knowledge gap concerning the genetic diversity distribution across marine invertebrates, and whether the latitudinal genetic diversity gradient results from congruent intraspecific trends. Here, we tested the hypotheses of the existence of a latitudinal mitochondrial genetic diversity gradient in marine decapods (crabs, hermit crabs, shrimps, lobsters) driven by environmental variables and that this gradient is the result of the accumulation of similar trends at the intraspecific level. We analyzed populational‐level cytochrome oxidase subunit I sequence available for Tropical Western Atlantic species (1883 sequences, 23 species) to investigate the association between mitochondrial genetic diversity versus latitude, and genetic diversity versus six environmental variables (sea surface temperature, dissolved oxygen, chlorophyll‐a, salinity, current velocity, pH). Intraspecific mitochondrial genetic diversity versus latitude analyses were also performed. Our findings indicate higher mitochondrial genetic diversity in lower latitudes (latitudinal genetic diversity gradient) driven by productivity and oxygen levels (only for nucleotide diversity). However, this trend is not caused by the accumulation of intraspecific patterns, which can be variable and species‐specific. Our results indicate that different levels of biological organization can show discordant patterns and suggest caution when interpreting macroscale investigations.